Keanekaragaman Tumbuhan Paku Pohon (Cyatheaceae) di Lereng Gunung Slamet, Kawasan Curug Cipendok - Palupi, Dian; Lestari, Sri; Desi Aryani, Riska; Hasna Dyah Kusumardani (Biotropic : The Journal of Tropical Biology, 2025)
Tree ferns of the family Cyatheaceae play an important role in maintaining the ecological balance of tropical montane forest ecosystems and are known for their sensitivity to microenvironmental variation. This study aimed to explore the species diversity and altitudinal distribution of Cyatheaceae in the lower montane rainforest of Curug Cipendok, located on the southern slope of Mount Slamet, Central Java, Indonesia. Field surveys were conducted using purposive sampling across three elevation zones (700–800 masl, 801–900 masl, and 901–1,000 masl). A total of six species comprising 396 individuals were recorded: Alsophila borneensis, A. firma, Cyathea aspera, C. schiedeana, Sphaeropteris glauca, and S. horrida. Species composition varied with elevation, with the highest diversity index (H’ = 1.722) found at mid-elevation. Morphological variations in trunk, fronds, and sori provided significant diagnostic information for taxonomic identification.